2018
DOI: 10.1021/acs.jpca.8b02598
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of the Interactions in Triethanolammonium-Based Ionic Liquids. A Quantum Chemical Study

Abstract: Structural features and interionic interactions play a crucial role in determining the overall stability of ionic liquids and their physicochemical properties. Therefore, we performed high-level quantum-chemical study of different cation-anion pairs representing the building units of protic ionic liquids based on triethanolammonium cation and anions of sulfuric, nitric, phosphoric, and phosphorus acids to provide essential insight into these phenomena at the molecular level. It was shown that every structure i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 74 publications
0
13
0
Order By: Relevance
“…The geometry of each species were optimized using density functional theory based Becke’s three parameter Lee–Yang–Parr exchange and correlation functional (B3LYP) method , employing the 6-31++G­(d,p) basis set. The B3LYP functional is often the method used for estimating the structural parameters and interionic interaction strengths in the ionic systems because of its higher accuracy and less computational workload. ,,, Addition, an empirical dispersion correction to hybrid functional (B3LYP-GD3) was incorporated due to presence of noncovalent interactions in the investigated compounds. To obtain the structures of the ion pairs, we started from the optimized geometry of the individual molecules of triethylamine and acid.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The geometry of each species were optimized using density functional theory based Becke’s three parameter Lee–Yang–Parr exchange and correlation functional (B3LYP) method , employing the 6-31++G­(d,p) basis set. The B3LYP functional is often the method used for estimating the structural parameters and interionic interaction strengths in the ionic systems because of its higher accuracy and less computational workload. ,,, Addition, an empirical dispersion correction to hybrid functional (B3LYP-GD3) was incorporated due to presence of noncovalent interactions in the investigated compounds. To obtain the structures of the ion pairs, we started from the optimized geometry of the individual molecules of triethylamine and acid.…”
Section: Methodsmentioning
confidence: 99%
“…The presence of hydroxyl groups in the structure of ammonium cation (when passing from triethyl-to triethanolammonium cation) leads to an increase in overall energetic stability of the ion pair with anion of phosphorous acid but to no strengthening of hydrogen bond. 32 Additionally, it was shown that the NH group of triethanolammonium cation has more proton donor-like character than the OH group that makes the N−H•••O hydrogen bonds stronger. Despite the growing amount of experimental work including the synthesis and study of the physicochemical properties of PILs based on triethylamine with benzoic, 33,34 phosphorous, 35 phosphoric, 36−39 and sulfonic 33,35−38,40−47 acids, there are still many questions about the microstructure of these compounds, interionic interactions and features of H-bonding.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The changes in the structure of TEOA cation in the ion pairs compared with the cation geometry itself (Figure S5 and Table S3, this in-deep structure analysis was performed earlier 22 ) are as follows: there is a distortion in the structure of TEOA cation in all investigated ion pairs owing to the presence of multiple hydrogen-bonding interactions between the cation and anion in them. None of the optimized ion pair structures have a tricyclic protrane structure within the cation that is characteristic of the solid phase.…”
Section: ■ Results and Discussionmentioning
confidence: 91%
“…We showed recently that the simultaneous formation of multiple H bonds between TEOA cation and inorganic anion (HSO 4 , NO 3 , H 2 PO 4 , H 2 PO 3 ) in the single hydrogen-bonded ion pair has a great influence on the geometry of TEOA cation. 22 The N−H•••O and O−H•••O hydrogen bonds between the cation and anion in these ion pairs are strongly coupled with the electrostatic interactions, and together they cause the loss of the structural symmetry of the cation itself. The three N−H(•••O) 3 distances within the cation being not identical in the ion pair structures are in the range of 2.74− 3.02 Å that are somewhat larger than the sums of vdW OH .…”
Section: ■ Introductionmentioning
confidence: 99%